The efects of whey protein and resistant starch on body weight - Malekian, Fatemah; Sebhatu Gebrelul, Sebhatu; Henson, James F; Cyrus, Kasundra D.; Goita, Mfamara; Kennedy, Betty M. (Functional foods in health and disease, 2015)
Background: Obesity is widely recognized as one of the most critical health threats to families and children across the country.  Obesity is a very serious health problem for people in Louisiana and especially in African Americans Children with 40.5% in the State classified as either overweight or obese as compared to 41.2% nationally. African American women have the highest rates of being overweight or obese (79.8%) compared to non-Hispanic whites (57.9%). In 2007, African Americans were 1.4 times as likely to be obese as whites. Therefore this study was designed to test the impact of dietary whey protein (WP) and resistant starch (RS) shakes/smoothies on reduction of body fat via increased satiety and increased energy expenditure in African Americans. Methods: Twenty eight African American males and females, age 21-43 years old were randomly divided into two groups.  For a period of 24-weeks, the treatment group consumed WP and RS shakes/smoothies for breakfast and received nutrition education. For the same period, the control group consumed the same shake/smoothies but with starch powder and received nutrition education. The data was analyzed using SAS version 9.3. Results: At the end of the 24 week study, the treatment group lost a mean body weight of approximately 7 kg (P ≤ 0.008) that was significantly different from the control group (P ≤ 0.209). In addition, the treatment group exhibited a significant decrease of ~6 cm in waist circumference (P ≤ 0.023).  There was no significant effect on mean blood pressure in treatment and control group.Conclusion: The findings from this study suggest that a combination of WP and RS in the form of shake/smoothie consumed for breakfast along with a nutrition education component may be an effective method in decreasing body weight, improving waist circumferences and cumulative food intake in African American males and females. Key Words:  Whey Protein, Resistant Starch, Obesity, Breakfast shakes, Nutrition education